2009
DOI: 10.1111/j.1471-4159.2009.06164.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of ATXN1 at Ser776 in the cerebellum

Abstract: Spinocerebellar ataxia type 1 (SCA1) is one of nine inherited neurodegenerative disorders caused by a mutant protein with an expanded polyglutamine tract. Phosphorylation of ataxin‐1 (ATXN1) at serine 776 is implicated in SCA1 pathogenesis. Previous studies, utilizing transfected cell lines and a Drosophila photoreceptor model of SCA1, suggest that phosphorylating ATXN1 at S776 renders it less susceptible to degradation. This work also indicated that oncogene from AKR mouse thymoma (Akt) promotes the phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 46 publications
3
58
0
Order By: Relevance
“…1f). Recently, Jorgenson et al [34] reported that Akt is not the cerebellar ataxin-1-S776 kinase and proposed the cyclic AMP-dependent protein kinase as a candidate S776 kinase. However, it is still unclear which kinase is the "human" cerebellar ataxin-1-S776 kinase, and which isoform of 14-3-3 proteins is most effective in and responsible for stabilization of the phosphorylation of the "human" cerebellar ataxin-1-S776.…”
Section: Ataxin-1 and 14-3-3 Proteinsmentioning
confidence: 98%
“…1f). Recently, Jorgenson et al [34] reported that Akt is not the cerebellar ataxin-1-S776 kinase and proposed the cyclic AMP-dependent protein kinase as a candidate S776 kinase. However, it is still unclear which kinase is the "human" cerebellar ataxin-1-S776 kinase, and which isoform of 14-3-3 proteins is most effective in and responsible for stabilization of the phosphorylation of the "human" cerebellar ataxin-1-S776.…”
Section: Ataxin-1 and 14-3-3 Proteinsmentioning
confidence: 98%
“…Building on our previous discovery that ATXN1 levels are highly sensitive to phosphorylation at residue S776 (mutation of serine to alanine decreases both ATXN1 stability and toxicity) 20,29 , we investigated whether the MAPK pathway kinases (MEK, ERK and MSK1) recovered in our screens phosphorylate ATXN1 at S776. This residue falls within the consensus phosphorylation sequence RXXS that is conserved in ATXN1 homologues (Fig.…”
Section: Msk1 Stabilizes Atxn1 By Phosphorylating S776mentioning
confidence: 99%
“…Further to polyQ expansion and nuclear localization, phosphorylation of S776 has been identified as a condition necessary for development of SCA1 (Emamian et al, 2003). Phosphorylation of S776 has been confirmed to occur in vivo (Emamian et al, 2003;Jorgensen et al, 2009) and is required for recognition of ataxin-1 by the protein 14-3-3, a molecular adaptor which modulates, in a phosphorylation-dependent manner, the function of different proteins in their specific context (Chen et al, 2003). Mutation of S776 to an alanine in expanded ataxin-1, despite not affecting nuclear localization, prevented the development of the SCA1 phenotype (Emamian et al, 2003).…”
Section: Prediction Of Elms In the C-terminal Iur: A Three-way Molecumentioning
confidence: 99%
“…Among all the predicted phosphorylation sites only the ones which have been confirmed in vivo and are supportive of the prediction of other phosphopeptide motifs have been included. a Phosphorylation site and kinase experimentally confirmed in cerebellum (Jorgensen et al, 2009). b Phosphorylation site confirmed, kinase not identified (Dephoure et al, 2008;Vierra-Green et al, 2005) putative phosphorylation-dependent protein-protein interaction motifs are predicted in the N-terminus of ataxin-1.…”
Section: Prediction Of Significant Elms In the N-terminal Iurmentioning
confidence: 99%
See 1 more Smart Citation